Introduction to the Basic Concepts of Modern Physics Special Relativity, Quantum and Statistical Physics - Becchi, Carlo Maria; D'Elia, Massimo (Undergraduate Lecture Notes in Physics, 2016)
This is the third edition of a well-received textbook on modern physics theory. This book provides an elementary but rigorous and self-contained presentation of the simplest theoretical framework that will meet the needs of undergraduate students. In addition, a number of examples of relevant applications and an appropriate list of solved problems are provided.Apart from a substantial extension of the proposed problems, the new edition provides more detailed discussion on Lorentz transformations and their group properties, a deeper treatment of quantum mechanics in a central potential, and a closer comparison of statistical mechanics in classical and in quantum physics. The first part of the book is devoted to special relativity, with a particular focus on space-time relativity and relativistic kinematics. The second part deals with Schrödinger's formulation of quantum mechanics. The presentation concerns mainly one-dimensional problems, but some three-dimensional examples are discussed in detail. The third part addresses the application of Gibbs' statistical methods to quantum systems and in particular to Bose and Fermi gases.